A Novel Temozolomide-Myricetin Drug-Drug Cocrystal: Preparation, Characterization, Property Evaluations - Qin, Hai-Xin; Wang, Jie; Peng, Jia-Hui; Dai, Xia-Lin; Li, Cai-Wen; Lu, Tong-Bu; Chen, Jia-Mei (Pharmaceutics, 2025)
Objectives: Drug-drug cocrystals with improved properties can be used to facilitate the development of synergistic therapeutic combinations. The goal of the present study is to obtain novel drug-drug cocrystals involving two anti-glioma agents, temozolomide (TMZ) and myricetin (MYR). Methods: The novel TMZ-MYR cocrystal was prepared via slurry and solvent evaporation techniques and characterized by X-ray diffraction, thermal analysis, infrared spectroscopy, and dynamic vapor sorption measurements. The stability, compaction, and dissolution properties were also evaluated. Results: Crystal structure analysis revealed that the cocrystal lattice contains two TMZ molecules, one MYR molecule, and four water molecules, which are linked by hydrogen bonding interactions to produce a three-dimensional network. The cocrystal hydrate exhibited favorable stability and tabletability compared to pure TMZ. A dissolution study showed that the maximum solubility of MYR in the cocrystal (176.4 μg/mL) was approximately 6.6 times higher than that of pure MYR·H2O (26.9 μg/mL), while the solubility of TMZ from the cocrystal (786.7 µg/mL) was remarkably lower than that of pure TMZ (7519.8 µg/mL). The solubility difference between MYR and TMZ was diminished from ~280-fold to ~4.5-fold. Conclusions: Overall, the TMZ-MYR cocrystal optimizes the stability and tabletability of TMZ and the dissolution behavior of both drugs, offering a promising approach for synergistic anti-glioma therapy with improved clinical potential.